CYP2D6 Allele Frequency in Five Malaria Vivax Endemic Areas From Brazilian Amazon Region - Salles, Paula Ferreira; Perce-da-Silva, Daiana Souza; Rossi, Atila Duque; Raposo, Luisa Riehl; Ramirez Ramirez, Aina Danaisa; Pereira Bastos, Otílio Machado; Pratt-Riccio, Lilian Rose; Cassiano, Gustavo Capatti; Baptista, Andrea Regina Souza; Cardoso, Cynthia Chester; Banic, Dalma Maria; Machado, Ricardo Luiz Dantas (Frontiers in Pharmacology, 2021)
Genetic variability was linked with individual responses to treatment and susceptibility to malaria by Plasmodium vivax. Polymorphisms in the CYP2D6 gene may modulate enzyme level and activity, thereby affecting individual responses to pharmacological treatment. The aim of the study was to investigate whether or not CYP2D6 single nucleotide polymorphisms (SNPs) rs1065852, rs38920-97, rs16947 and rs28371725 are unequally distributed in malaria by Plasmodium vivax individuals from the Brazilian Amazon region. The blood samples were collected from 220 unrelated Plasmodium vivax patients from five different endemic areas. Genotyping was performed using SNaPshot® and real-time PCR methods. In all five areas, the rs1065852 (CYP2D6*10, C.100C>T), rs3892097 (CYP2D6*4, 1846C>T) and rs16947 (CYP2D6*2, C.2850G>A), as a homozygous genotype, showed the lowest frequencies. The rs28371725 (CYP2D6*41, 2988G>A) homozygous genotype was not detected, while the allele A was found in a single patient from Macapá region. No deviations from Hardy-Weinberg equilibrium were found, although a borderline p-value was observed (p = 0.048) for the SNP rs3892097 in Goianésia do Pará, Pará state. No significant associations were detected in these frequencies among the five studied areas. For the SNP rs3892097, a higher frequency was observed for the C/T heterozygous genotype in the Plácido de Castro and Macapá, Acre and Amapá states, respectively. The distribution of the CYP2D6 alleles investigated in the different areas of the Brazilian Amazon is not homogeneous. Further investigations are necessary in order to determine which alleles might be informative to assure optimal drug dosing recommendations based on experimental pharmacogenetics.